Gender-responsive approaches to rapid climate warming among smallholder farmers - Akyala, A.; Ayanlade, A.; Adeyeye, O.; Oluwatimilehin, I.A. (Elsevier, 2023)
Climate change impact has no global and gender boundary, yet how gender norms mediate crop farmers' responsive approaches to rapid climate warming received little attention. Men and women crop smallholder farmers in Nasarawa state experience the impacts of rapid climate warming differently. This study examines the gender-responsive approaches to rapid climate warming among crop smallholder farmers in Nasarawa. Temperature data for 36 years was used to establish change. Also, a survey of semi-strcutured questionnaire with in-depth interviews (IDIs) was conducted among 52 smallholder farmers consisting of men and women in agriculture. Participants for the study were selected using a purposive sampling technique. Descriptive statistics, including time series analysis and frequency distribution was used to analyse the temperature data in R. The results from the analysis of temperature data are on graphs and charts. While data from the questionnaire were analysed using descriptive statistics, content analysis was used to analyse the transcripts of IDI and further presented in themes. The results from this study revealed that there has been an additional increase of 1.14°C in the minimum temperature of the study area over the study period. Analysis showed a statistical trend in the time series of the maximum temperature from January to May throughout the study period and no statistical trend in the minimum temperature time series data for all months (January to December. More so, 63% of respondents perceived both heatwaves and dry spells, while 21% perceived only heatwaves. Also from the results, 33% of the respondents perceived only dry spells as an indication of rapid warming. From the results, the major adaptation strategies used by farmers are traditional irrigation (56%), sustainable forestry (44%), and cover cropping (54%). The results indicated that 66% of women adopted the traditional irrigation practice and 75% practised cover cropping. On the other hand, a larger percentage of men (74%) practised sustainable forestry. Findings showed that gender norms constrain the adoption of responsive approaches which could be as a result of unequal access to climate interventions in agriculture. This study recommends the equitable distribution of climate intervention and capacity-building programs among men and women to help them build resilience to rapid climate warming.